Sentido e não-sentido: a hospitalidade em situações de sofrimento extremo - Costella, Silvério (2016)
Research directs a phenomenological reflection centered on Levinas, as an hospitality illuminator to the human being suffering in the extreme situations of existence. It is possible to reframing the psychotherapeutic support in the extreme situations of suffering. In this sense, the ethical support was also named as a therapeutic modality. The past where psychoanalysis focused on the origin of suffering in order to interpret and give meaning to the present moment, in the ethical sense, it has no history, considering the instant itself a relationship, an achievement without this relationship refers to "a future or an any past." The ethical signification is given to the present moment, from the ethical therapeutic support without having to reframing the last instant to mean the next instant. This instant has a beginning, a middle and an end. Being has no beginning, “it is as if starts there”, because time is discontinuous, timeless, infinite. From this new ethical and therapeutic meaning, sense or no sense is no longer reduced to the good position of the subject, as it occurred in the ontology. Therapeutic ethics does not hold the reconstruction of the ego of the other. However, it searches for a meaning from the hospitality even thought in the strange subjectivity, completely different, psychotic, which can support the other better than one in the structured ego. This means that it is possible to emerge sense and ethic signification in the destruction of the subject. The sense is a gift that can be achieved to everybody regardless of success or failure in the real world.